Neocalanus cristatus (Copepoda) From a Deep Sediment-Trap: Abundance and Implications for Ecological and Biogeochemical Studies - Ikenoue, Takahito; Otosaka, Shigeyoshi; Honda, Makio C.; Kitamura, Minoru; Mino, Yoshihisa; Narita, Hisashi; Kobayashi, Takuya (Frontiers in Marine Science, 2022)
We studied seasonal variations of the mesozooplankton swimmer community collected by a sediment trap moored at 873 m in the Kuroshio–Oyashio Transition region off the east coast of Japan from 5 August 2011 to 23 June 2013, with sampling bottles rotating at 26-day intervals. The total flux of mesozooplankton swimmers varied between 0 and 11.1 individuals m–2 d–1, with a mean of 3.1 individuals m–2 d–1 during the sampling period. In total, 89 taxa were found in the trap material, of which copepods comprised 87.1% of all swimmers on average. Among the Copepoda, Neocalanus cristatus was the most dominant taxon (76.2% of copepods on average during the sampling period), and all of them were stage C5 copepodite to adult. The species composition of the swimmers closely reflected the mesopelagic mesozooplankton of the Oyashio region. Because all N. cristatus observed in the trap were stage C5 to adult, its flux represents a time series of variations in life history and response to environmental changes at the depth of the sediment trap. The fluxes of Neocalanus species (N. cristatus, N. flemingeri, and N. plumchrus) reflected ontogenetic vertical migration, but may have been overestimates of active fluxes if they included dormant individuals that accidentally entered the sediment trap. The apparent active carbon flux of Neocalanus species ranged from 0 to 22.3 mg C m–2 d–1 during the sampling period, with a mean value of 4.9 mg C m–2 d–1.